WEB-BASED OUTDOOR EQUIPMENT RENTAL INFORMATION SYSTEM AT IN OUTDOORS - Muhammad Afin Amirullah; Ade Eviyanti; Hamzah = Setiawan; Novia Atiyanti (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to develop a web-based outdoor equipment rental information system designed to facilitate efficient and structured management of equipment rental and borrowing processes. Method: The research employed a system development approach involving stages of analysis, design, implementation, and testing to address issues commonly found in manual rental management, such as stock recording, scheduling, and transaction reporting. Results: The developed system successfully streamlines administrative tasks by enabling real-time monitoring of equipment availability, simplifying the ordering process, and allowing users to track loan status efficiently. This integration reduces time consumption and minimizes human error in data recording and transaction handling. Novelty: The study presents an innovative web-based solution that enhances transparency, accessibility, and operational efficiency in outdoor equipment rental management, offering a practical model that can be adapted for similar rental service systems in various sectors.